Capacity Building of TVET Trainers in a Developing Country Through Practice-oriented Curriculum Implementation - Park, Seungchul; Park, Hyeseung (Journal of Technical Education and Training, 2025)
It is well recognized through numerous development cases that fostering high-quality technical human resources through excellent TVET (Technical and Vocational Education and Training) is crucial for the sustainable economic development of developing countries. The key to the advancement of TVET lies in effectively training high-quality trainers who possess both theoretical and practical educational capabilities to deliver training that aligns with industry demands. However, due to limited national support and lack of capacity building opportunities, the quality of TVET trainers in most developing countries remains inadequate. As a result, this leads to a shortage of high-quality technical human resources, which becomes a significant obstacle to sustainable economic development of corresponding country. Therefore, official development assistance aimed at promoting sustainable economic growth in these countries needs to prioritize the TVET sector, with particular emphasis on strengthening the competencies of TVET trainers. This study presents a case in which the capacity building of trainers at the FTVTI (Federal TVET Institute) in Ethiopia, a national university that trains TVET trainers, was effectively supported through a curriculum revision and related activities focused on practice-oriented education, as part of a project implemented by KOICA (Korea International Cooperation Agency). This case is expected to serve as a valuable reference for the sustainable capacity building of TVET trainers in developing countries through official development assistance in the future.